Alcohol Consumption and the Risk for Developing Pancreatitis. Issue 1 (January 2015) - Kume, Kiyoshi; Masamune, Atsushi; Ariga, Hiroyuki; Shimosegawa, Tooru
<x xml:space="preserve">Abstract</x> Objective This study aimed to estimate the association of alcohol consumption and pancreatitis in Japan. Methods We performed a nationwide case-control study, which included 982 patients (574 patients with acute pancreatitis and 408 patients with chronic pancreatitis) and 1015 controls who were individually matched for sex, age, hospital, and time of their first hospital visit. Conditional logistic regression was used to assess the association of alcohol consumption and smoking with pancreatitis. Results The patients had a mean (SD) age of 57.6 (17.0) years; 71.8% were male. Compared with nondrinkers, alcohol consumption of less than 20 g/d was not associated with the risk for total pancreatitis (odds ratio [OR], 1.0; 95% confidence interval [CI], 0.7–1.4). In patients with acute pancreatitis, the ORs (95% CI) for alcohol consumption of 20 ⩽ ∼ < 40 g/d, 40 ⩽ ∼ < 60 g/d, 60 ⩽ ∼ < 80 g/d, 80 ⩽ ∼ < 100 g/d, and 100 g/d or greater were 1.7 (0.9–3.0), 3.1 (1.6–5.9), 4.2 (2.1–8.2), 5.3 (2.4–12.0), and 6.4 (3.4–12.4), respectively. In patients with chronic pancreatitis, the ORs (95% CI) for alcohol consumption of 20 ⩽ ∼ < 40 g/d, 40 ⩽ ∼ < 60 g/d, 60 ⩽ ∼ < 80 g/d, 80 ⩽ ∼ < 100 g/d, and 100 g/d or greater were 2.6 (1.2–5.5), 3.2 (1.5–7.1), 9.2 (4.1–20.3), 13.0 (5.3–31.6), and 19.6 (8.2–46.8), respectively. Conclusions Our study precisely measured the quantitative effect of alcohol on the risk for developing pancreatitis.